Enhanced lipid productivity in AGP knockout marine microalga Tetraselmis sp. using a DNA-free CRISPR-Cas9 RNP method. (May 2020) - Chang, Kwang Suk; Kim, Jongrae; Park, Hanwool; Hong, Seong-Joo; Lee, Choul-Gyun; Jin, EonSeon
Highlights: AGP locus in Tetraslemis sp. was mutated by CRISPR-Cas9 RNP. AGP mutants showed enhanced lipid production and the absence of starch synthesis. Fatty acids in AGP mutants increased by 274% and 314% compared to that in wild type. AGP mutants showed 2.3- and 2.7-fold higher lipid productivity than the wild type. Abstract: A marine green microalga, Tetraselmis sp., has been studied for the production of biomass and lipids in seawater culture. Since carbohydrate and lipid biosynthesis are competitive metabolic pathways, we attempted to increase lipid synthesis in Tetraselmis by inhibiting carbohydrate synthesis. The main regulatory enzyme in the starch synthesis pathway is ADP-glucose pyrophosphorylase (AGP). AGP loss-of-function mutants were developed using the CRISPR-Cas9 ribonucleoprotein (RNP) delivery system. AGP mutants showed a slight decrease in growth. However, the lipid content in two AGP mutants was significantly enhanced by 2.7 and 3.1 fold (21.1% and 24.1% of DCW), respectively, compared to that in the wild type (7.68% of DCW) under nitrogen starvation. This study is an example of metabolic engineering by genetic editing using the CRISPR-Cas9 RNP method in marine green microalgae. Consequently, starchless Tetraselmis mutants might be considered potential producers of lipids in seawater cultures.